Genetics of hypertension in populations affected by the Aral Sea ecological crisis: A case-control study - Khurshid Ataniyazov; Darya Vladimirovna Zakirova; Khurshid Meylikov; Gulnoz Khamidullaeva; Guzal Abdullaeva; Shahlo Turdikulova; Khurshid Fozilov; Alisher Abdullaev (PLoS ONE, 2026)
Objective This research investigates the correlation between nine polymorphic variants and the incidence of hypertension and its clinical manifestations in the Ellikqala District in the Republic of Karakalpakstan, Uzbekistan. This district is known as one of the most challenging areas for human habitation due to its high salinity levels in the environment, which contribute to a higher prevalence of cardiovascular diseases. Methods This was a population-based case-control study. The study included 801 participants from the Karakalpakstan region of Uzbekistan, of which 621 were patients with essential hypertension, and the remaining 180 were the control group. Genetic analysis was conducted using multiplex qPCR with allele-specific probes. A statistical approach based on logistic regression was applied to identify their association with essential hypertension and its clinical manifestations. Logistic regression under a log-additive genetic model was used to calculate unadjusted (crude) and adjusted odds ratios and 95% confidence intervals. Stratified analyses by sex, age (<60 vs. ≥ 60 years), and BMI (<25 vs. ≥ 25 kg/m²) were performed with Bonferroni correction (k = 18 per stratification; threshold p < 2.8e-3). Results The analysis revealed statistically significant associations between essential hypertension and six polymorphic variants after Bonferroni correction (k = 9, corrected threshold: p < 5.6e-3): AGT C521T (rs4762; OR = 0.12, 95% CI: 0.08–0.16, p-Bonferroni = 2.99e-50), AGT T704C (rs699; OR = 0.68, 95% CI: 0.54–0.86, p-Bonferroni = 1.1979e-2), AGTR2 G1675A (rs1403543; OR = 0.52, 95% CI: 0.42–0.64, p-Bonferroni = 4.76e-9), CYP11B2 C(−344)T (rs1799998; OR = 0.47, 95% CI: 0.36–0.60, p-Bonferroni = 8.97e-9), GNB3 C825T (rs5443; OR = 1.66, 95% CI: 1.27–2.18, p-Bonferroni = 1.368e-3), and NOS3 T(−786)C (rs2070744; OR = 0.27, 95% CI: 0.21–0.34, p-Bonferroni = 2.50e-27). NOS3 G894T (rs1799983) showed a nominally significant association prior to correction (OR = 0.68, 95% CI: 0.52–0.89; p = 5.069e-3), but did not survive Bonferroni adjustment (p-Bonferroni = 4.5621e-2) and should be interpreted with caution. Conclusion Six out of nine studied polymorphic variants were associated with essential hypertension and its clinical manifestations in the Ellikqala District in the Republic of Karakalpakstan, Uzbekistan.